A novel relationship between elastic modulus and void ratio associated with principal stress for coral calcareous sand - Gao, Ran; Ye, Jianhong (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Elastic moduli, e.g. shear modulus G and bulk modulus K, are important parameters of geotechnical materials, which are not only the indices for the evaluation of the deformation ability of soils but also the important basic parameters for the development of the constitutive models of geotechnical materials. In this study, a series of triaxial loading-unloading-reloading shear tests and isotropic loading-unloading-reloading tests are conducted to study several typical mechanical properties of coral calcareous sand (CCS), and the void ratio evolution during loading, unloading and reloading. The test results show that the stress-strain curves during multiple unloading processes are almost parallel, and their slopes are much greater than the deformation modulus at the initial stage of loading. The relationship between the confining pressure and the volumetric strain can be defined approximately by a hyperbolic equation under the condition of monotonic loading of confining pressure. Under the condition of confining pressure unloading, the evolution of void ratio is linear in the e-lnp′ plane, and these lines are a series of almost parallel lines if there are multiple processes of unloading. Based on the experimental results, it is found that the modified Hardin formulae for the elastic modulus estimation have a significant deviation from the tested values for CCS. Based on the experimental results, it is proposed that the elastic modulus of soils should be determined by the intersection line of two spatial surfaces in the G/K-e-p'/pa space (pa: atmosphere pressure). “Ye formulation” is further proposed for the estimation of the elastic modulus of CCS. This new estimation formulation for soil elastic modulus would provide a new method to accurately describe the mechanical behavior of granular soils. •A series of triaxial loading-unloading-reloading shear tests and isotropic loading-unloading-reloading tests are conducted.•Several typical mechanical properties of coral calcareous sand (CCS) are explored.•A novel relationship for elastic modulus with void ratio and mean principal stress for granular materials is proposed.•The newly proposed relationship will be helpful for the development of constitutive model for granular soils.